The Interface Between Metacognitive Strategy Training and Locus of Control in Developing EFL Learners’ Listening Comprehension Skill - Taherkhani, Bahador; Aliasin, Seyed Hesamuddin; Khosravi, Robab; Izadpanah, Siros (Frontiers in Education, 2022)
This study investigated the effects of metacognitive listening strategy instruction (MLSI) and learners’ locus of control orientation on the listening comprehension of EFL learners. 100 EFL students at the University of Zanjan and Imam Khomeini International University of Qazvin were randomly chosen. The participants were randomly assigned to an experimental group (N = 50) and a control group (N = 50). The experimental group received 10 weeks of treatment including 10 sessions of metacognitive listening strategy training. Both groups took the Metacognitive Awareness Listening Questionnaire and Rotter’s Internal-External Locus of Control Scale before the treatment sessions. Then, they took the listening pre-test and after the treatment, the listening post-test was administered and the required data was obtained. The findings revealed that MLSI had a significant impact on the learners’ listening comprehension for the learners with internal LoC; However, external LoC did not have any significant moderating effect on listening comprehension ability. Pedagogical implications are suggested for an EFL teaching/learning context.